2022
DOI: 10.1038/s41598-022-09888-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the Naples prognostic score for patients with non-small-cell lung cancer

Abstract: The Naples prognostic score (NPS) is an effective inflammatory and nutritional scoring system widely applied as a prognostic factor in various cancers. We aimed to analyze the prognostic value of the NPS in patients diagnosed with non-small-cell lung cancer (NSCLC). We prospectively collected 395 patients diagnosed with NSCLC between January 2016 and December 2018 in two university-affiliated hospitals. Patients were divided into three groups according to their pretreatment NPS (Group 0: NPS = 0; Group 1: NPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…9 The Naples prognostic score (NPS), a scoring system using albumin, total cholesterol, and inflammation cells, has been used to predict the presence, severity, and prognosis of patients with various cardiac conditions. [10][11][12] Although there have been several studies investigating the effectiveness of albumin, cholesterol, and inflammatory cells, there is limited data evaluating the value of the Naples score in predicting the presence and severity of CAD. 13,14 The aim of the present study is to investigate the correlation between coronary severity and the NPS and SII scores in people with stable CAD.…”
Section: Introductionmentioning
confidence: 99%
“…9 The Naples prognostic score (NPS), a scoring system using albumin, total cholesterol, and inflammation cells, has been used to predict the presence, severity, and prognosis of patients with various cardiac conditions. [10][11][12] Although there have been several studies investigating the effectiveness of albumin, cholesterol, and inflammatory cells, there is limited data evaluating the value of the Naples score in predicting the presence and severity of CAD. 13,14 The aim of the present study is to investigate the correlation between coronary severity and the NPS and SII scores in people with stable CAD.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that a marker with limited predictive ability cannot be applied to a wide variety of cases. To evaluate the prognosis of patients, several scoring systems have been developed, which incorporate various parameters like NPS, CONUT, and SIS [ 8 , 10 , 18 , 24 ]. These systems have been increasingly used in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In their research, Peng et al found that NPS can be a useful predictor for overall survey and progression-free survival in non-small cell lung cancer patients, regardless of their TNM stage [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Naples prognostic score (NPS) is a scoring system comprising NLR and LMR, reflective of inflammation, along with albumin and total cholesterol, indicators of malnutrition [14]. While NPS has been extensively explored in cancer patients [14][15][16], its applicability in cardiovascular research remains limited. This study aimed to assess the prognostic potential of NPS in predicting in-hospital mortality in the context of STEMI, bridging the gap in evidence within cardiovascular research.…”
Section: Introductionmentioning
confidence: 99%